THE GEOGRAPHICAL FACTOR IN THE POLITICAL HISTORY OF DJAR-BELOKANI IN THE 18TH CENTURY - Halaev, Zahid Alievic (History, Archeology and Ethnography of the Caucasus, 2023)
Any socio-political institution should be considered in the context of the geographical environment in which it develops. The geographical factor throughout history has been exceptionally strong. Any society in the historical process, one way or another, not only adapted to the environment, but also impacted the environment itself. Despite the great role of the geographical factor in the historical retrospective, today this problem is on the periphery of the interests of Russian Caucasian studies. We believe that, without describing the degree of influence of the geographical factor on the political development of the Djar-Belokani societies in the 18th century it is impossible to understand the peculiarities of their political position and historical development. The paper highlights the issue of the influence of the geographical factor on the political development of the Djar-Belokani unions of societies in the 18th century, poorly studied in Russian Caucasian studies. The paper reveals the influence of the geographical factor on the genesis and social structure, administrative and political management, socio-political development of the Djar-Belokani societies in the 18th century. The union consisted of five rural communities: Dzharsky, Belokansky, Talsky, Mukhakhsky and Dzhinikhsky. Geographically, it was separated by the Alazan River from Kakheti, in the north it adjoined the southern spurs of the Main Caucasian Range, in the east and southeast it bordered on the Elisu Sultanate. The societies of the Djar-Belokani Union occupied a very rich territory in terms of natural and geographical terms. According to the nature of the relief and the peculiarities of the natural conditions, the lands of the union were divided into two physical and geographical regions – lowland and foothill. In turn, these areas are represented by even more fractional zones and micro-zones, differing in the originality of the landscape and climate.